1997
DOI: 10.1016/s1097-2765(00)80016-7
|View full text |Cite
|
Sign up to set email alerts
|

Terminal Intron Dinucleotide Sequences Do Not Distinguish between U2- and U12-Dependent Introns

Abstract: Two types of eukaryotic nuclear introns are known: the common U2-dependent class with /GU and AG/ terminal intron dinucleotides, and the rare U12-dependent class with /AU and AC/ termini. Here we show that the U12-dependent splicing system can splice introns with /GU and AG/ termini and that such introns occur naturally. Further, U2-dependent introns with /AU and AC/termini also occur naturally and are evolutionarily conserved. Thus, the sequence of the terminal dinucleotides does not determine which spliceoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
155
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 112 publications
(165 citation statements)
references
References 32 publications
9
155
0
Order By: Relevance
“…The sensitivity of the U12-dependent 59 splice site to inactivation by mutation is striking+ In addition to the double mutations described here, we have shown that a single point mutation of position C 5 to G in the context of mutation of the terminal intron nucleotides to G was sufficient to convert the U12-dependent 59 splice site into a U2-dependent 59 splice site (Dietrich et al+, 1997)+ An equally striking finding is the very high degree of FIGURE 4. Allelic specificity of suppression of P120 mutations at positions 4 and 5 of the 59 splice site sequence by U6atac snRNA mutants+ The P120 59 splice site mutants indicated at the top were cotransfected with the U6atac expression alleles indicated above each lane+ Splicing of the wild-type P120 minigene is shown in lane 1+ The analysis and presentation is the same as in Figure 3+ conservation of these nucleotides in all known examples of U12-dependent introns (Sharp & Burge, 1997;Tarn & Steitz, 1997;Wu & Krainer, 1997)+ The results described here show that the major role of these nucleotides is to base pair with the appropriate snRNAs+ Thus, the splicing of U12-dependent introns appears to be substantially more dependent on specific RNA-RNA base pairing than does U2-dependent splicing, where much more variation in splice site sequences is tolerated+ An interesting aspect of these results is that, although it is possible to draw potential base pairs between the 59 splice site and both U11 and U6atac throughout the same region of the 59 splice site ( Figs+ 1B, 2A), there appear to be subregions of this sequence where interactions with one or the other snRNA are more important in the in vivo rescue assay+ For example, toward the 59 end of the region, U6atac can suppress mutations alone, whereas, toward the 39 end, U11 snRNA can suppress mutations alone+ In the middle of this region, when the C 5 C 6 dinucleotide of the 59 splice site is changed to GG, suppressor alleles of both U11 and U6atac snRNAs are required to maximally rescue the P120 mutation+ It is difficult in the context of the in vivo assay to determine the mechanistic causes of this result+ As discussed in more detail below, the activation of the U12-dependent 59 splice site is likely to involve the sequential interaction of U11 and U6atac snRNAs+ There is no a priori reason to believe that all the base pairs drawn in Figure 2A are of equal weight or that all of them are even present+ Some of the snRNA sequences may not be available for base pairing in the native snRNP structure+ For example, the lack of significant U11 suppression of mutations at positions 4 and 5 of the 59 splice site may reflect the inaccessibility of U11 positions 7 and 8 due to the proximity of these residues to the 59 stem-loop structure of U11 snRNA (see Fig+ 1B)+ Alternatively, mispairing with wild-type U6atac may be better tolerated in cases where the mutations are farther away from the U6atac-U12 interaction region than when they are closer+ Because in vivo suppression of the 59 splice site mutations is likely to be the result of both selection and activation of the 59 splice site, these issues may need to be investigated at the biochemical level+…”
Section: Mutants Of U6atac Suppress the Splicing Defect Of 59 Splice mentioning
confidence: 59%
See 2 more Smart Citations
“…The sensitivity of the U12-dependent 59 splice site to inactivation by mutation is striking+ In addition to the double mutations described here, we have shown that a single point mutation of position C 5 to G in the context of mutation of the terminal intron nucleotides to G was sufficient to convert the U12-dependent 59 splice site into a U2-dependent 59 splice site (Dietrich et al+, 1997)+ An equally striking finding is the very high degree of FIGURE 4. Allelic specificity of suppression of P120 mutations at positions 4 and 5 of the 59 splice site sequence by U6atac snRNA mutants+ The P120 59 splice site mutants indicated at the top were cotransfected with the U6atac expression alleles indicated above each lane+ Splicing of the wild-type P120 minigene is shown in lane 1+ The analysis and presentation is the same as in Figure 3+ conservation of these nucleotides in all known examples of U12-dependent introns (Sharp & Burge, 1997;Tarn & Steitz, 1997;Wu & Krainer, 1997)+ The results described here show that the major role of these nucleotides is to base pair with the appropriate snRNAs+ Thus, the splicing of U12-dependent introns appears to be substantially more dependent on specific RNA-RNA base pairing than does U2-dependent splicing, where much more variation in splice site sequences is tolerated+ An interesting aspect of these results is that, although it is possible to draw potential base pairs between the 59 splice site and both U11 and U6atac throughout the same region of the 59 splice site ( Figs+ 1B, 2A), there appear to be subregions of this sequence where interactions with one or the other snRNA are more important in the in vivo rescue assay+ For example, toward the 59 end of the region, U6atac can suppress mutations alone, whereas, toward the 39 end, U11 snRNA can suppress mutations alone+ In the middle of this region, when the C 5 C 6 dinucleotide of the 59 splice site is changed to GG, suppressor alleles of both U11 and U6atac snRNAs are required to maximally rescue the P120 mutation+ It is difficult in the context of the in vivo assay to determine the mechanistic causes of this result+ As discussed in more detail below, the activation of the U12-dependent 59 splice site is likely to involve the sequential interaction of U11 and U6atac snRNAs+ There is no a priori reason to believe that all the base pairs drawn in Figure 2A are of equal weight or that all of them are even present+ Some of the snRNA sequences may not be available for base pairing in the native snRNP structure+ For example, the lack of significant U11 suppression of mutations at positions 4 and 5 of the 59 splice site may reflect the inaccessibility of U11 positions 7 and 8 due to the proximity of these residues to the 59 stem-loop structure of U11 snRNA (see Fig+ 1B)+ Alternatively, mispairing with wild-type U6atac may be better tolerated in cases where the mutations are farther away from the U6atac-U12 interaction region than when they are closer+ Because in vivo suppression of the 59 splice site mutations is likely to be the result of both selection and activation of the 59 splice site, these issues may need to be investigated at the biochemical level+…”
Section: Mutants Of U6atac Suppress the Splicing Defect Of 59 Splice mentioning
confidence: 59%
“…The minor snRNA species U11, U12, U4atac, and U6atac appear to be the functional analogues of U1, U2, U4, and U6, respectively, at least to a first approximation+ U5 snRNA appears to be common to both systems+ Both in vivo and in vitro data support the idea that U12 snRNA interacts by base pairing with the highly conserved branch site sequence (Hall & Padgett, 1996;Tarn & Steitz, 1996a) and U11 snRNA interacts similarly with at least a portion of the 59 splice site sequence (Kolossova & Padgett, 1997;Yu & Steitz, 1997)+ Because these distinctive biochemical requirements define the two spliceosomal systems rather than any one feature of the intronic splice sites, we refer to the two classes of introns as U2-dependent or U12-dependent (Dietrich et al+, 1997)+ Recently, a novel U6-like snRNA called U6atac snRNA was identified that appears to be the functional analogue of U6 snRNA in the U12-dependent splicing system (Tarn & Steitz, 1996b)+ This finding has provided an opportunity to examine the conservation of some of the RNA-RNA interactions believed to be central to the splicing process+ One candidate interaction that emerged directly from the comparison of the U6 and U6atac snRNA sequences was the potential for base pairing between the U12-dependent 59 splice site and U6atac+ U6 snRNA contains a phylogenetically highly conserved sequence of ACAGA located just 59 of a region known to base pair with U2 snRNA in the spliceosome (Fig+ 1A)+ This sequence has been shown to interact, at least partially by base pairing, with the 59 splice site and, in particular, with the conserved G at position ϩ5 (Kandels- Lewis & Seraphin, 1993;Lesser & Guthrie, 1993;Hwang & Cohen, 1996)+ In U6atac snRNA, this sequence is replaced by AAGGAGA, which is also located 59 of a region that can potentially form base pairs with U12 snRNA and where a U12-U6atac in vitro crosslink has been mapped (Tarn & Steitz, 1996b)+ As shown in the shaded region of Figure 1B, this U6atac sequence has the potential to form several base pairs with the 59 splice site sequence of U12-dependent introns by displacing U11 snRNA+ In support of this idea, a recent crosslinking study detected an interaction between the 59 splice site of a U12-dependent intron and U6atac (Yu & Steitz, 1997)+ However, the site of crosslinking on U6atac was not determined and the functional significance of this crosslink remains to be shown+ To examine this potential U6atac snRNA-59 splice site interaction in an in vivo functional context, we examined the ability of specifically mutated U6atac snRNAs to rescue splicing of a U12-dependent intron containing splicing-defective mutations in the highly conserved 59 splice site sequence+ Our previous experiments looking for suppression of these intron mutants by mutant U11 snRNAs showed that splicing of some but not all 59 splice site mutants could be rescued (Kolossova & Padgett, 1997)+ We proposed that a possible reason for the inability of U11 snRNA mutations to suppress other 59 splice site mutations might be due to a requirement fo...…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Introns belonging to these two distinct classes are spliced by two different spliceosomes: the major U2-type spliceosome and the less abundant U12-type spliceosome (Hall and Padgett, 1996;Tarn and Steitz 1996a. Although the first U12 introns to be described had AT-AC-terminal dinucleotides, the majority of U12-type introns contain GT-AG, and a small number contain other noncanonical terminal dinucleotides, such as AT-AA, AT-AG, AT-AT, GT-AT, or GT-GG (Jackson, 1991;Hall and Padgett, 1994;Dietrich et al, 1997Dietrich et al, , 2001aSharp and Burge, 1997;Burge et al, 1998;Wu and Krainer, 1999;Levine and Durbin, 2001;Zhu and Brendel, 2003). Moreover, functional analyses have shown that AT-AC-terminal dinucleotides are not a defining feature of U12 introns (Dietrich et al, 1997(Dietrich et al, , 2001a.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first U12 introns to be described had AT-AC-terminal dinucleotides, the majority of U12-type introns contain GT-AG, and a small number contain other noncanonical terminal dinucleotides, such as AT-AA, AT-AG, AT-AT, GT-AT, or GT-GG (Jackson, 1991;Hall and Padgett, 1994;Dietrich et al, 1997Dietrich et al, , 2001aSharp and Burge, 1997;Burge et al, 1998;Wu and Krainer, 1999;Levine and Durbin, 2001;Zhu and Brendel, 2003). Moreover, functional analyses have shown that AT-AC-terminal dinucleotides are not a defining feature of U12 introns (Dietrich et al, 1997(Dietrich et al, , 2001a. Instead, U12 introns contain highly conserved sequences in the 59 splice site (exon:G/ATATCCTY) and branchpoint region (TCCTTRAY) (Hall and Padgett, 1994;Sharp and Burge, 1997;Burge et al, 1998), which are both required for prespliceosome complex formation (Frilander and Steitz, 1999).…”
mentioning
confidence: 99%